Senescent Thyrocytes, Similarly to Thyroid Tumor Cells, Elicit M2-like Macrophage Polarization In Vivo - Mara Mazzoni; Giuseppe Mauro; Lucia Minoli; Loredana Cleris; Maria Chiara Anania; Tiziana Di Marco; Emanuela Minna; Sonia Pagliardini; Maria Grazia Rizzetti; Giacomo Manenti; Maria Grazia Borrello; Eugenio Scanziani; et al. (Biology, 2021)
Inflammation plays a critical role in thyroid cancer onset and progression. We previously characterized the in vitro interplay between macrophages and senescent human thyrocytes and thyroid tumor-derived cell lines, modeling the early and the late thyroid tumor phases, respectively. We reported that both models are able to induce pro-tumoral M2-like macrophage polarization, through the activation of the COX2-PGE2 axis. Here, we investigated the presence of macrophage infiltrating cells in mouse xenografts derived from the above described cells models. We showed that subcutaneous injection in immunodeficient mice of both senescent human thyrocytes and thyroid tumor-derived cell lines elicits macrophage recruitment. Furthermore, considering the type of macrophage infiltrate, we observed a stronger infiltration of Arginase I positive cells (M2-like). Overall, these results demonstrate the in vivo capability of senescent and tumor thyroid cells to recruit and polarize macrophages, suggesting that the promotion of a pro-tumoral microenvironment through tumor associated macrophages may occurs in late as well as in early thyroid tumor stages, favoring tumor onset and progression.